Possible HSP reactivation post‐COVID‐19 vaccination and booster - Makoto Kondo (Wiley, 2021)
Abstract A 45‐year‐old woman with a history of Henoch‐Schönlein (HSP) purpura received COVID‐19 vaccination. The patient showed HSP reactivation after COVID‐19 vaccination and booster. In HSP, autoimmune memory of vasculitis persists and might be reactivated with COVID‐19 vaccination.